Analisis Pengaruh Kualitas Produk, Harga, Kualitas Pelayanan, Dan Promosi Terhadap Kepuasan Konsumen Pada Toko Kue Xyz Di Jakarta - Sylvia Permata Sari (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to find out the variables that affect the customer satisfaction, this research is conducted in order to find out whether quality of product, price, quality of service, and promotion influence the customer satisfaction at xyz cake store in jakarta . analysis tool used to measure the influence of the elements mentioned above are multiple linear regression. Based on the analysis, it can be concluded that simultaneously the variable of product (X1), quality of service (X2), price (X3), and promotion (X4) influence the customer satisfaction (Y). it is also consluded that partially (individual)The quality of product, price, quality of service, and promotion influence the customer satisfaction. the result shows that quality of product and quality of service have the most impact significantly on customer satisfaction of cake product at xyz cake store.